Structural refinement and photoluminescence properties of cube-like (Ca 1-xCu x)TiO 3 crystals synthesized by the microwave-hydrothermal method - Oliveira, Larissa H.; De Moura, Ana P. [UNESP]; Cavalcante, Laécio S. [UNESP]; Antonio, Selma G. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (My University, 2012)
In this work, (Ca 1-xCu x)TiO 3 crystals with (x = 0, 0.01 and 0.02), labeled as CTO, CCTO1 and CCTO2, were synthesized by the microwave-hydrothermal method at 140°C for 32 min. XRD patterns (Fig. 1), Rietveld refinement and FT-Raman spectroscopy indicated that these crystals present orthorhombic structure Pbnm. Micro-Raman and XANES spectra suggested that the substitution of Ca by Cu in A-site promoted a displacement of the [TiO6]-[TiO6] clusters adjacent from its symmetric center, which leads distortions on the [CaO 12] clusters neighboring and consequently cause the strains into the CaTiO3 lattice. FE-SEM images showed that these crystals have an irregular shape as cube like probably indicating an Ostwald-ripening and self-assemble as dominant mechanisms to crystals growth. The powders presented an intense PL blue-emission.
Keywords: Chemical synthesis; Luminescence; Microcrystals; Optical materials; XANES; Blue-emission; Dominant mechanism; FT- Raman spectroscopy; Irregular shape; Micro-Raman; Microwave-hydrothermal methods; Orthorhombic structures; Photoluminescence properties; Self-assemble; Structural refinement; TiO; XANES spectra; XRD patterns; Calcium; Crystal growth; Crystal structure; Exhibitions; Films; Nanotechnology; Ostwald ripening; Perovskite; Raman spectroscopy; Rietveld refinement; Nanocomposite films